Hak Pekerja Perspektif Sayyid Quṭb dalam Tafsir Fī Ẓilāl Al-Qur’ān - M Wardaya (Yayasan Albahriah Jamiah Indonesia, 2025)
This research is based on the modern social reality that is still characterized by injustice and violations of workers’ rights, both in the form of labor exploitation, wage inequality, and marginalization of humanitarian values ​​that should be the foundation of work ethics. This phenomenon indicates an urgent need to reinterpret the values ​​of justice in the Qur’an that place humans as dignified subjects in the production process. Based on this context, the research aims to uncover the construction of Sayyid Quṭb’s interpretation of workers’ rights and social justice as stated in his monumental work, Fī Ẓilāl Al-Qur’ān. This research uses a qualitative approach with thematic interpretation analysis method (tafsīr mauḍūʻī), which explores the verses of the Qur’an related to work, wages, social responsibility, and the principle of economic justice. The results show that Sayyid Quṭb views work not only as an economic activity, but also as a form of worship and a manifestation of devotion to God that emphasizes spiritual values ​​in human productive activities. He rejected all forms of exploitation that diminish the dignity of workers and emphasized that the relationship between workers and employers must be built on a balance of rights and obligations, not the dominance of one party. In Quṭb’s view, the ideal Islamic social system creates distributive justice that ensures shared prosperity, with the state playing an active role in upholding fair and ethical economic mechanisms. The implications of this research enrich the discourse on social interpretation of the Qur’an, while also offering conceptual contributions to the formation of an Islamic work ethic and a worker protection system grounded in the values ​​of justice, humanity, and holistic social responsibility.